TECHNICAL, ECONOMIC AND LEGAL ASPECTS REGARDING THE EVOLUTION OF AFRICAN SWINE PLAGUES IN ROMANIA - Romeo Cătălin CREŢU; Petrică ŞTEFAN; Silviu Ionuţ BEIA; Silviu Viorel ANDREI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
African swine plague causes great economic losses due to the catastrophic depopulation of pig farms in the areas affected by their death and slaughter, by the implementation of approved sanitary measures and trade restrictions. African swine plague is a transboundary disease that can spread rapidly from one country to another and is one of the most dangerous diseases of pigs, being included in list A of „The World Organization for Animal Health (OIE)”. In this paper we analyzed some technical aspects related to the occurrence and evolution of African swine plague in the world and in our country. Due to the extremely rapid evolution of this disease in south-eastern Europe and especially in Romania, we considered it very important to analyze the economic aspects of this virus, especially the damages produced, and to see what the applicable European and national laws African swine plague and whether these normative acts have been enforced and respected in preventing the onset and transmission of the disease.